Pengaruh Fungsi Audit Internal Terhadap Fee Auditor Eksternal (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2022) - Yulianti, Yulianti; Hidayat, Rahmat; Jamilah, Wardah; Zakiyyatunnisa, Yuchana (Jurnal Etnik: Ekonomi-Teknik, 2023)
The effect of the internal audit function on external auditor fees is an important consideration in determining the cost of auditing and monitoring the company. This study aims to provide empirical evidence regarding the effect of the internal audit function on external auditor fees. This type of research is a quantitative analysis using descriptive statistical methods. This study uses secondary data from the annual reports of mining companies listed on the Indonesia Stock Exchange in 2021-2022. This study uses purposive sampling method and uses simple linear regression as an analysis instrument. Based on the test results conducted using the classical assumption test and simple linear regression analysis techniques, it can be concluded that the internal audit function has no significant effect on external auditor fees. Although the results of this study indicate that there is no significant effect between the internal audit function and external auditor fees, there are also several other studies that have successfully examined that the internal audit function has a significant effect on external auditor fees.